Investigation of the Role of AT2 Receptors in the Nucleus Tractus Solitarii of Normotensive Rats in Blood Pressure Control - Légat, Laura; Smolders, Ilse J.; Dupont, Alain G. (Frontiers in Neuroscience, 2019)
Aim: The nucleus tractus solitarii (NTS) densely expresses angiotensin II type 2 receptors (AT2R), which are mainly located on inhibitory gamma-aminobutyric acid (GABA) neurons. Central AT2R stimulation reduces blood pressure, and AT2R stimulation in the rostral ventrolateral medulla (RVLM), mediates a hypotensive response through a GABAergic mechanism. We aimed to test the hypothesis that an AT2R mediated inhibition of the GABA release within the NTS might be involved in this hypotensive response, by assessing possible alterations in blood pressure and heart rate, as well as in GABA levels in normotensive Wistar rats. Methods: In vivo microdialysis was used for measurement of extracellular GABA levels and for perfusion of the selective AT2R agonist, Compound 21, within the NTS. Our set-up allowed to determine simultaneously the excitatory glutamate dialysate levels. The mean arterial pressure and heart rate responses were monitored with a pressure transducer. Results: Local perfusion of Compound 21 into the NTS did not modify blood pressure and heart rate, nor glutamate and GABA levels compared to baseline concentrations. A putative effect was also not unmasked by concomitant angiotensin II type 1 receptor blockade with candesartan. Positive control experiments confirmed that the experimental set up had enough sensitivity to detect a reduction in GABA dialysate levels and blood pressure. Conclusion: The results did not provide evidence for a role of the AT2R within the NTS in the control of blood pressure, nor for an interaction with local GABAergic signaling in normotensive rats.